Manual Physical Therapists’ Use of Biopsychosocial History Taking in the Management of Patients with Back or Neck Pain in Clinical Practice - Rob A. B. Oostendorp; Hans Elvers; Emilia Mikołajewska; Marjan Laekeman; Emiel van Trijffel; Han Samwel; William Duquet (The Scientific World Journal)
Objective. To develop and evaluate process indicators relevant to biopsychosocial history taking in patients with chronic back and neck pain. Methods. The SCEBS method, covering the Somatic, Psychological (Cognition, Emotion, and Behavior), and Social dimensions of chronic pain, was used to evaluate biopsychosocial history taking by manual physical therapists (MPTs). In Phase I, process indicators were developed while in Phase II indicators were tested in practice. Results. Literature-based recommendations were transformed into 51 process indicators. Twenty MTPs contributed 108 patient audio recordings. History taking was excellent (98.3%) for the Somatic dimension, very inadequate for Cognition (43.1%) and Behavior (38.3%), weak (27.8%) for Emotion, and low (18.2%) for the Social dimension. MTPs estimated their coverage of the Somatic dimension as excellent (100%), as adequate for Cognition, Emotion, and Behavior (60.1%), and as very inadequate for the Social dimension (39.8%). Conclusion. MTPs perform screening for musculoskeletal pain mainly through the use of somatic dimension of (chronic) pain. Psychological and social dimensions of chronic pain were inadequately covered by MPTs. Furthermore, a substantial discrepancy between actual and self-estimated use of biopsychosocial history taking was noted. We strongly recommend full implementation of the SCEBS method in educational programs in manual physical therapy.